(untitled) (International Journal of Environmental Sciences, 2025)
A significant global issue involves environmental contamination, particularly by heavy metal ions found in wastewater. It is usual practice to tackle this problem using ion exchange, chemical precipitation, coagulation, membrane separation, reverse osmosis, and adsorption procedures. In order to purify wastewater of various heavy metal ions, especially those that have proved harmful to living things, a wide range of adsorbents have been produced. In this paper, investigates the effectiveness of Red Mud (RM) as an adsorbent for removing contaminants from industrial wastewater. RM, a byproduct of alumina production, was utilized due to its potential to adsorb heavy metals and other pollutants effectively. This research focused on optimizing various parameters such as pH, adsorbent dosage, contact time, and initial concentration of contaminants to enhance adsorption efficiency. Both Langmuir and Freundlich isotherm models were employed to analyze the adsorption equilibrium, showing favorable adsorption characteristics with high correlation coefficients. The study concludes that RM holds promise as a sustainable and cost-effective adsorbent for treating industrial wastewater, offering significant potential for environmental remediation efforts. The experimental findings demonstrate that RM achieved a maximum adsorption capacity (qm) of 13.33 mg/g according to the Langmuir isotherm, and a Freundlich isotherm yielded a maximum value of n = 2.21 for red mud.